Urbanization and floods in the Seoul Metropolitan area of South Korea: What old maps tell us. (July 2019) - Bae, Sunhak; Chang, Heejun
Abstract: This study examined how land cover change, topographic, and socioeconomic factors affect flood damage in the Seoul metropolitan area of South Korea that has experienced rapid economic growth and urbanization for the last 30 years. We used geographic information system and spatial regression analysis for identifying explanatory factors for each ten years from 1985 to 2014. A unique aspect of this study is how land use history could explain the spatial variation of flood damage using an old map created in the early 20th century. Our results show that high flood damage areas are spatially clustered in the outskirts of the study area where rapid urbanization happened. Population density was the common factor that best explained flood damage in all three periods. The percentage of farmland and the percentage of urban area were positively and negatively associated with flood damage in 1990 and 2000, respectively. Fiscal self-reliance ratio and previous flood damage were negatively and positively related to flood damage in 2010, respectively. In the early stage of urban expansion, the conversion of agricultural land to urban land was associated with increasing flood damage. As urbanization continued and matured, the conversion of forest areas to urban areas better explained the spatial variation of flood damage. This study demonstrates the importance of historical land use for understanding urban floods and shows that factors affecting flood damage have changed over time, suggesting the need for different flood management strategies to minimize flood damage as urbanization progresses.